Extending the Useful Life of Dye-2 to 1986. Part I: Preliminary Findings and Recommendations. - Tobiasson,Wayne; Korhonen,Charles; Redfield,Robert (1979)
Dew Line Ice Cap Station DYE-2 appears to need major work within the next few years to extend its useful life to 1986. The structural steel frame is overstressed in a few areas and the lower portion of the subsurface timber truss enclosure is in bad condition. Additional performance measurements are needed during 1979 to determine the rate of secondary stress in the structural steel frame and the rate of deterioration of the truss enclosure. With this information a decision can be made whether to move the building sideways onto a new undistorted foundation or to stabilize it in-place by encapsulating the lower 52 ft of the substructure in ice.